2001
DOI: 10.1046/j.1570-7458.2001.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the aggregative response of the blue willow beetle, Phratora vulgatissima

Abstract: Factors influencing the aggregative response of the blue willow beetle, Phratora vulgatissima (L.) (Coleoptera: Chrysomelidae), on potted plants of Salix dasyclados (Wimm) were investigated in the field. A significantly higher female beetle density was recorded on plants that had a combination of beetle‐feeding damage and conspecific beetles present as compared with control plants and plants having only damage or beetles. Volatile chemicals emitted from undamaged S. dasyclados (Wimm) leaves were found to be be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…There was also no evidence that beetles were choosing trees on the basis of leaf number, as there were very few associations between beetle damage and leaves per tree. Beetles may be responding to other factors, such as conspecifics or kairomones, as shown previously (Peacock, Lewis & Herrick 2001). This plant choice behaviour makes predictions of insect movement, especially in relation to configuration of genotypes within a plantation, very difficult.…”
Section: Discussionmentioning
confidence: 87%
“…There was also no evidence that beetles were choosing trees on the basis of leaf number, as there were very few associations between beetle damage and leaves per tree. Beetles may be responding to other factors, such as conspecifics or kairomones, as shown previously (Peacock, Lewis & Herrick 2001). This plant choice behaviour makes predictions of insect movement, especially in relation to configuration of genotypes within a plantation, very difficult.…”
Section: Discussionmentioning
confidence: 87%
“…Adults emerge in August, feed quickly, and find hibernation sites. Adults probably excrete pheromones that attract other individuals (Peacock et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…How this species evaluates occupancy is not fully understood. Herbivory combined with beetle presence attracts other adults, suggesting that plant volatiles and pheromones are involved (Peacock et al 2001), but other cues might also help determine occupancy (Fernandez andHilker 2007, Dicke andBaldwin 2010). Early eggs probably contributed more to the final number of eggs on a plant than later eggs because females probably laid fewer eggs as they encountered more eggs on a plant over the course of the experiment.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…It has already been reported that behavioral responses of arthropods to plant volatiles can be affected by gender and hunger levels (Landolt et al 1999;Shimoda and Dicke 2000;Peacock et al 2001). For example, olfactory responses of the predatory mite Phytoseiulus persimilis to odor from lima bean plants infested by their prey, Tetranychus urticae, depend on the hunger levels of the predatory mites (Sabelis and van de Baan 1983;Shimoda and Dicke 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, olfactory responses of the predatory mite Phytoseiulus persimilis to odor from lima bean plants infested by their prey, Tetranychus urticae, depend on the hunger levels of the predatory mites (Sabelis and van de Baan 1983;Shimoda and Dicke 2000). Also, females, but not males, of chrysomelid leaf beetles, such as Phratora vulgatissima and Leptinotarsa decemlineata, are attracted to odor from plants infested by conspecifics (Landolt et al 1999;Peacock et al 2001). Thus, to test our hypothesis, we focused on hunger levels and gender of P. versicolora.…”
Section: Introductionmentioning
confidence: 99%